Miracle holdings: probiotics straw / Muhammd Haziq Hazman Mohd Rusli... [et al.] - Mohd Rusli, Muhammd Haziq Hazman; Harayadi, Mohammad Nazran; Zainal, Irfan Hashimi; Hakimi, Muhammad Firdaus; Sopian, Syaiful Hamzah; Mohamad, Muhammad Ali (2018)
This Anti-Diabetic Straw is specially made to reduce the glucose intake in your drinks. Our main target market is to any user that have diabetic disease.